Lupus-associated NCF2 variant p.R395W in the NADPH oxidase 2 complex results in a reduced production of reactive oxygen species by myeloid cells - Song, Zhimin; Yoo, Dae-Goon; Idol, Rachel A.; Barbu, Emilia Alina; Jacob, Chaim O.; Dinauer, Mary C. (Frontiers in Lupus, 2023)
The leukocyte NADPH oxidase 2 (NOX2) generates superoxide, and derivative reactive oxygen species play important roles in both host defense and immunoregulation. The rs13306575 genetic variant, resulting in an Arginine395→Tryptophan (R395W) substitution in the NOX2 NCF2 subunit, is associated with an increased risk of lupus in patients of Hispanic-American or of Korean ancestry. Arginine395 resides within the NCF2 PB1 domain, and participates in a constitutive high-affinity interaction with the NOX2 NCF4 subunit to stabilize their expression. However, whether this variant impacts NCF2 function and NOX2 activity is unknown. To answer this question, mice expressing NCF2-R395W were generated using CRISPR/Cas9. NCF2 and NCF4 expression were reduced by 2-fold in neutrophils, macrophages and dendritic cells homozygous for NCF2-R395W. Moreover, following stimulation with soluble or particulate stimuli, ROS production at the plasma membrane and within cells was reduced in all three myeloid lineages expressing NCF2-R395W. Additional studies on Ncf2+/- mice, which have reduced expression of wild-type NCF2 but not NCF4, suggest that the reduced expression of both NCF2 and NCF4 contributes to the diminished NOX2 activity in NCF2-R395 mice. These results establish that the lupus-associated rs13306575 p.R395W allele is a functional hypomorph. The findings add to growing evidence implicating deficient NOX2 activity in the pathogenesis of lupus.